Automatización de una Máquina Sopladora Uniloy Milacron (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2011)
The automation of a blower machine MILACRON Uniloy MODEL 1995 owned by HGT Engineering is performed, for preparation of their own blowing products. In order to achieve the automation of the equipment, the critical variables in the processes of blowing, extrusion and drawing of the parison were determined, aimed to establish the proper sequence for operation of the machine. Subsequently, the control system was designed and the most suitable parts for controlling the above processes were selected. After that, the board that controls the blowing machine either manually or automatically was designed, as well as the human-machine interface for proper operation of the equipment. Finally, the selected components are installed in the machine to testing and tuning the system.
Keywords: Automation; blowing; control; programming